Espaços desconstruídos livres no centro de Ribeirão Preto - Silva, Denise Elaine Simões da (2015)
When mankind began its relationship with nature, the space started to suffer transformations as a consequence of this interaction. The urban landscape of the cities, seen as a mixture of new and old spatial interventions and directly related to destructions, the modifications and possible vestiges of natural space appear as a scenario that must be studied, understood and diagnosed. “space deconstruction” stands right in the recovery of this totality, the essence of constructions and anthropic actions; as a new way of looking at the city we are producing. The present dissertation proposes to identify and classify the “free deconstructed spaces” of a perimeter selected from the central quadrilateral region of Ribeirão Preto, São Paulo, Brazil (the historical center of Ribeirão Preto), indicating likely areas to receiving possible occupations of social interest housing and urban public policy instruments that can motivate such actions and make them feasible. In light of this, analysis criteria were created based on the typologies of the “minimal deconstruction”, as a method to characterize and hierarchize these spaces. The results allowed us to identify requalification processes of central areas of the cities, while not only conserving a greater constructive and architectural patrimony, but also engaging them socially.